Developing an insulation box with automatic temperature control for PM2.5 measurements in cold regions. (1st June 2022) - Yasunari, Teppei J.; Wakabayashi, Shigeto; Matsumi, Yutaka; Matoba, Sumito
Abstract: Low-cost PM2.5 sensors are now used worldwide to assess air pollution. However, their operation is generally challenging in severely cold regions like Siberia, Alaska, the Arctic, and Antarctica. We made an insulation box with automatic internal temperature control developed for a low-cost PM2.5 sensor to maintain a warm operational environment with four light-bulb heaters when the air temperature inside of the insulation box falls slightly below 5 °C under the current preset temperature setting. We confirmed the performance of the temperature controller with four light-bulb heaters in a −25 °C cold temperature room. In addition, we found that the insulation box must be attached to a small electric fan to forcibly ventilate the box to accurately reflect the external ambient air conditions into the insulating box. Our observations with the data from our low-cost PM2.5 sensor fitted with the insulation box were validated against the Sapporo National Ambient Air Monitoring Station (NAAMS) data in Sapporo, Japan, showing good correspondence with the hourly station-measured data. Then, we installed our PM2.5 measurement system on the roof of the International Arctic Research Center (IARC), University of Alaska Fairbanks, Alaska, USA, in June 2019. The sensor sufficiently captured two instances of significant increases in PM2.5 mass concentrations during the Alaskan wildfires in the summer of 2019. Our developed insulation box for low-cost PM2.5 sensors, called "the portable PM2.5 measurement system for cold regions", will help assess air quality in many cold regions in future studies. Highlights: The insulation box developed for the low-cost PM2.5 sensor worked well in a −25 °C cold temperature room. Forced ventilation had to be used to reflect external air conditions. Data collected using the sensor inside the insulation box (portable system) corresponded well with station-acquired data in Sapporo, Japan. The sensor accurately measured two significant increases in PM2.5 concentrations during Alaskan wildfires. Our system presented here is useful to measure PM2.5 throughout the year in temporarily or permanently cold regions.